2009
DOI: 10.1029/2008ja013898
|View full text |Cite
|
Sign up to set email alerts
|

Possible evidence of virtual resonance in the dayside magnetosphere

Abstract: [1] On day 108, 2001, the Sub-Auroral Magnetometer Network (SAMNET) and Magnetometers along the Eastern Atlantic Seaboard for Undergraduate Research and Education (MEASURE) magnetometer arrays detected dayside magnetic pulsations at a common frequency of $15 mHz at all locations below L = 4. This global pulsation event was associated with alignment of the interplanetary magnetic field with the Sun-Earth axis, a condition known to generate ultralow-frequency (ULF) waves in front of the bow shock. The event occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
3
13
1
Order By: Relevance
“…Thus far, the ground magnetometer observations are more consistent with the PVR model, considering that the Pi2 pulsations were observed outside the plasmapause as well as inside (Figure ). Moreover, the ground magnetometer phase relationships are consistent with those found in previous observational studies of PVR [ Takahashi et al , ]. However, for pulsations observed near and just outside the plasmapause, we cannot rule out the possibility of a field line resonance (FLR) which has been reported to show polarization change associated with the plasmapause in previous studies [e.g., Fukunishi , ].…”
Section: Observations and Analysissupporting
confidence: 86%
“…Thus far, the ground magnetometer observations are more consistent with the PVR model, considering that the Pi2 pulsations were observed outside the plasmapause as well as inside (Figure ). Moreover, the ground magnetometer phase relationships are consistent with those found in previous observational studies of PVR [ Takahashi et al , ]. However, for pulsations observed near and just outside the plasmapause, we cannot rule out the possibility of a field line resonance (FLR) which has been reported to show polarization change associated with the plasmapause in previous studies [e.g., Fukunishi , ].…”
Section: Observations and Analysissupporting
confidence: 86%
“…The 8 mHz wave observations are consistent with models of radially standing MHD fast mode waves such as PVR: same frequency observed across a wide range of latitude/longitude, frequency does not change through multiple intensifications as long as the radial density/Alfvén speed profile does not change, very small time lags between signals observed at stations separated by 3.5 h MLT suggest globally coherent wave activity with very small (∼0) azimuthal wave number, strong in situ electric field perturbations in conjunction with weak total magnetic field perturbations suggest nodal structure (Keiling & Takahashi, ; Li et al, ; Nosé et al, ). Phase differences between in situ electric field and ground‐based observations were also consistent with PVR during periods when the RBSP‐B electric field MGSE measurement was roughly aligned with the east‐west direction, and in situ and ground‐based measurements had a high degree of coherence, consistent with previous studies (Takahashi et al, ); for brevity sake we have not shown these observations. We shall refer to these waves as a PVR rather than another standing fast mode wave (e.g., plasmaspheric cavity mode) primarily due to observations in Figures and indicating the presence of monochromatic wave activity at latitudes mapping outside the plasmapause, particularly before 0700 UT.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, there is observational evidence for a dayside plasmaspheric cavity mode (Takahashi et al 2009) and its propagation to the night side (Takahashi et al 2005). Studies of such events could shed light on the role the plasmasphere commonly plays in trapping fast mode waves.…”
Section: Longitudinal Structurementioning
confidence: 97%